INCLUSIVE EDUCATION IN DIGITAL ERA: OPPORTUNITIES AND CHALLENGES FOR VIET NAM - HOANG MINH PHU (Tạp chí Khoa học xã hội Thành phố Hồ Chí Minh, 2025)
Implementing the inclusive education program for children with disabilities is one of the crucial tasks of the education sector, ensuring equality in education and creating learning opportunities for all. Similar to general education, in the current era of rapid scientific and technological advancement, applying advancements in science and technology to inclusive education programs for children with disabilities is essential to enhance educational effectiveness. In this article, through a comprehensive review of recent literature, the author introduces the concept of inclusive education and focuses on analyzing the opportunities and challenges in applying scientific and technological achievements into the inclusive education program in Vietnam. Based on this analysis, the author proposes suitable approaches for implementing inclusive education in Vietnam.